Management Of Extracurricular Munazharah Ilmiah: Implications For Critical Thinking Skills, Istima' And Kalam - Siddiq, Sayid Munadi; Isnaini, Rohmatun Lukluk (Ijaz Arabi Journal of Arabic Learning, 2025)
Learning activities to improve students' critical thinking skills are common. One of the activities that can enhance critical thinking skills is the munazharah ilmiah activity at the Ar Raayah Islamic boarding school. This study aims to find the management pattern of the munazharah ilmiah extracurricular activity and its implications for students' critical thinking, istima', and kalam skills at the Ar Raayah Islamic boarding school. This study uses a qualitative case study approach at the Ar Raayah Islamic boarding school. Data collection was carried out using interviews, observation, and documentation methods. The informants in this study were 16 students of STIBA Ar Raayah , extracurricular activity trainers, and teachers at the Ar Raayah Islamic boarding school. Data analysis consisted of reading/memoing, describing, and classifying. The study results showed that munazharah ilmiah, as an extracurricular activity, was held for students interested in participating in the Arabic debate competition. The discussion topics came from the handbook and were based on hot issues in social life. This activity was managed by the PBA Student Association (HIMA). This activity's trainers are students with experience in Arabic debate competitions. The rules in this activity follow the Qatar debate regulations and the debaters must use Arabic correctly and adequately. Munazharah ilmiah process that requires arguments trains students to think critically. The students' istima' ability is trained when listening to the opponent's argument. Likewise, the ability to write is trained when expressing arguments and rebuttals clearly and firmly in a short time. The management process of this munazharah ilmiah activity can be adopted by other Islamic boarding schools that want to train their students in critical thinking, istima', and kalam.